COVID-19-related fear and stress among individuals who experienced child abuse: The mediating effect of complex posttraumatic stress disorder. (December 2020) - Tsur, Noga; Abu-Raiya, Hisham
Abstract: Background: The COVID-19 pandemic exposes individuals not only to health-related risks, but also to psychosocial fear and acute stress. Previous studies reveal that individuals who experienced child abuse (CA), especially those who suffer from complex posttraumatic stress disorder (CPTSD), are at a higher risk of reacting with fear and stress when faced with stressful life-events. Objective: To test whether exposure to CA is implicated in a higher risk of COVID-19-related fear and acute stress, and whether CPTSD intervenes in such processes. Participants and settings: A convenience sample of 837 adults participated in the study during the first peak of COVID-19 in Israel. Methods: Participants completed self-report questionnaires, assessing child physical, sexual and emotional abuse, CPTSD (ITQ), COVID-19-related acute stress disorder (COVID-19 ASD; ASDS) and fear of COVID-19. Results: Bivariate analyses showed that participants who experienced CA were higher than participants who did not experience CA in COVID-19 ASD ( p = .032), but not in fear of COVID-19 ( p = .65). Mediation analyses demonstrated two significant paths: in the first, CA was associated with elevated fear of COVID-19 (effect = .061, .059; p < 0.05) and COVID-19 ASD (effect = .14, .084; p < 0.05) through the mediation of CPTSD; in the second path, when controlling for the mediation of CPTSD, CA was associated with reduced fear of COVID-19 (effect = −.15; p = 0.001), and COVID-19 ASD (effect = −.12; p = 0.024). Conclusions: The findings reveal a complex pattern, indicating that CPTSD may be a risk factor for elevated levels of COVID-19 distress among individuals who experienced CA. However, some CA survivors may express reduced COVID-19 distress.